Essays on agricultural development in Tanzania - Boulay, Basile (2018)
This thesis is made of three self-contained essays on the agricultural sector of Tanzania, each of them focusing on an aspect of direct policy relevance. In the first essay, I study whether an inverse relationship exists between cultivated area and physical productivity (yield per acre) for a set of important annual crops. I define size as the area of a plot on which a crop is grown, thus introducing a more disaggregated level of analysis than the common plot or crop levels of analysis. I control for the existing hypotheses in the literature potentially explaining this inverse relationship and propose to control for two new hypotheses which are only testable at this level of analysis.